Multiplex peptide microarray profiling of antibody reactivity against neglected tropical diseases derived B-cell epitopes for serodiagnosis in Zimbabwe - Arthur Vengesai; Thajasvarie Naicker; Herald Midzi; Maritha Kasambala; Tariro L Mduluza-Jokonya; Simbarashe Rusakaniko; Francisca Mutapi; Takafira Mduluza (Public Library of Science, 2022)
Introduction Peptides (B-cell epitopes) have broad applications in disease diagnosis and surveillance of pathogen exposure. In this framework, we present a pilot study to design and produce a peptide microarray for the integrated surveillance of neglected tropical diseases. The peptide microarray was evaluated against peptides derived from Ascaris lumbricoides , Necator americanus , Schistosoma haematobium , Schistosoma mansoni , Trichuris trichiura , Bacillus anthracis , Mycobacterium leprae , Wuchereria bancrofti , Rabies lyssavirus , Chlamydia trachomatis and Trypanosoma brucei . Methods S . haematobium was diagnosed using the urine filtration technique. S . mansoni , A . lumbricoides , N . americanus and T . trichiura were diagnosed using the Kato Katz and formal ether concentration techniques. Immunogenic peptides were retrieved from the Tackling Infection to Benefit Africa infectious diseases epitope microarray. Further peptides were predicted using ABCpred. IgG and IgM reactivity against the derived peptides were evaluated using peptide microarray multiplex immunoassays. Positive response was defined as fluorescence intensity ≥ 500 fluorescence units. Immunodominant peptides were identified using color-coded heat maps and bar graphs reflecting the obtained fluorescence signal intensities. Receiver Operating Characteristic analysis and Mann-Whitney-U test were performed to determine the diagnostic validity of the peptides. Results Species-specific responses with at least one peptide derived from each NTD pathogen were observed. The reactive peptides included; for S . haematobium , XP_035588858.1-206-220 and XP_035588858.1-206-220 immunodominant for IgG and IgM respectively, for S . mansoni , P20287.1-58-72 immunodominant for both antibodies and for T . trichiura , CDW52482.1-326-340 immunodominant for IgG and CDW57769.1-2017-2031 and CDW57769.1-1518-1532 immunodominant for IgM. According to ROC analysis most of the peptides selected were inaccurate; with AUC < 0.5. Some peptides had AUC values ranging from 0.5 to 0.5875 for both IgM and IgG suggesting no discrimination. Conclusion Multiplex peptide microarrays are a valuable tool for integrated NTDs surveillance and for screening parasites exposure in endemic areas. Species sero-reactivity observed in the study maybe indicative of exposure to the different NTDs parasites. However, although peptides with the least cross reactivity were selected there is need to validate the sero-reactivity with recombinant antigens and immune-blotting techniques such as western blotting.